The Effects of Visual Displays of Furniture Product Photos Through the Social Networking Site, Instagram on Consume Perception - Kirana, Dini Cinda; Syarief, Achmad; Saphiranti, Dona (Idealogy Journal, 2018)
At present, the growth of Instagram as an online site is phenomenal, because of the shift from its original function as a social communication medium into a marketing platform. Furniture products used to be only available for in-store purchase, can now be easily purchased online. The present study attempted to discover the level of influence and effectiveness of the visual appearance of the furniture products photos through the social networking site, Instagram on consumer perceptions, which is measured using the EPIC (Empathy, Persuasion, Impact and Communication) model. The purpose of the study was to identify the effectiveness of the visual display of furniture product photos on the Instagram social networking site on consumer’s perceptions, and to map the use of the ideal visual display of furniture product photos for online product marketing purposes. The research used comparative analytical methods on photos of furniture products from six accounts of small creative economy entrepreneurs of similar products that are advertised through the social networking site, Instagram. The data of this study are limited in the scope of visual perception of furniture product photos uploaded through the social networking site, Instagram on consumer perceptions. The results showed that the visual display in the form of photos of furniture products through the social networking site, Instagram had an effective result on consumer perceptions. The visual display is declared effective as a media for promoting furniture products through the social networking site, Instagram based on the four dimensions of EPIC. The dimensions of Empathy and Impact are the most dominant aspects. The visual display mapping used as an advertising photo is not only influenced by the Empathy dimension and the Impact dimension, but also dominantly influenced by the associated design principles, namely, Unity and Domination. Both dimensions have a significant correlation value compared to other dimensions. Keywords: Furniture Marketing, Instagram, Consumer Perception, EPIC Model, Design Principles